Cartografias sonoras: um estudo sobre o Documentário Sonoro do Folclore Brasileiro (1972-1998) - Ribeiro, Juliana Lima (2025)
This ethnographically grounded study aims to analyze the phonographic series Documentário Sonoro do Folclore Brasileiro (DSFB; 1972-1989) from a processualist perspective, seeking to understand how practices of selection, editing, and sound archiving contributed to the production of phonographic representations of the nation. Throughout its institutional trajectory, the series incorporated diverse forms of sonic representation of the national. By tracing the production of the documentary over three decades, this study seeks to demonstrate how continuities, ruptures, updates, and re-significations were embedded in the series’ temporality. The research’s central argument is that the DSFB was at the core of key initiatives to revive mobilization around folklore studies in the 1970s. Furthermore, the series played a significant role in highlighting institutional transformations in subsequent decades, driven by new research methodologies and epistemic.